Avaliação das modificações de histonas H3K36me3, H3K9ac, H4K12ac e H3S10ph em queilite actínica e carcinoma epidermóide de lábio - Freitas Filho, Silas Antonio Juvencio de (2015)
The actinic cheilitis (AC) and lip squamous cell carcinoma (LSCC) are caused by prolonged exposure to the ultraviolet radiation in sunlight. Histone modifications are epigenetic deregulation that are associated with diverse cellular processes such as, for example, transcription, replication, repair, and present in pathological processes such as cancer. The aim of this study was to investigate the expression of antigens related to histone modifications in AC and LSCC compared to normal tissue by immunohistochemistry. Were evaluated 33 samples of AC, 27 cases of LSCC and nine cases of normal mucosa lip, diagnosed in the Pathology Laboratory of the School of Dentistry, Federal University of Uberlandia, between 1978 and 2013. After histopathological review, immunohistochemical was performed with antibodies against H3K36me3, H3K9ac, H4K12ac and H3S10ph. The proportion of reactive cells and the intensity were evaluated through the Quickscore index. There was a significant reduction (p <0.05) of the immunohistochemical reactivity of H3S10ph and H3K36me3 in ACs and LSCCs when compared to normal mucosa lip. A statistically significant decrease was found for immunohistochemical reactivity of H3K9ac and H4K12ac compared to normal tissue, there was not differences between the normal mucosa lip and LSCC. There was a statistically significant association between H3K9ac and gender in patients with carcinomas. There was not a statistically significant result when comparing AC with mild to moderate/intense dysplasia, or between well-differentiated compared to moderately/poorly differentiated carcinomas. The variations in histone modifications evaluated are relevant to begin in the process of carcinogenesis, but not to tumor progression in actinic aggression lip.